A Case Report on Breast Carcinoma Co-Existing with Axillary Diffuse Large B Cell Lymphoma - Win Myat Oo; Sein Win; Nyein Chan Aung (Asian Journal of Medicine & Health Sciences, 2023)
Simultaneous presentation of invasive breast carcinoma and diffuse large B cell lymphoma is a rare condition. We presented a case of a 63-year-old lady with diffuse large B cell lymphoma in the right axillary lymph nodes and co-existing invasive breast carcinoma in the right breast. She noticed a lump in her right breast by self-examination in July 2021, but she did not seek medical attention for that lump. She again noticed another lump at the right axilla in August 2021, and another lump at left axilla in September 2021. Then she consulted a surgeon and base line investigations were done. All the investigations were normal except the mammogram, which showed cancer in the right breast. The right mastectomy and right axillary clearance operation was done. The lymph nodes sections showed normal lymphoid architecture were totally obliterated due to diffuse sheet of proliferation of medium size to large lymphoid cells. These neoplastic lymphoid cells were CD3-, CD5-, CD20+, BCL2+, CD10-, BCL6-, Cmyc-, MUM1- with high Ki67 expression and it matched with diffuse large B cell lymphoma, activated B cell phenotype. The breast tumor mass showed normal architecture was effaced due to proliferation of neoplastic uniform epithelial cells which were dispersed as a single strand within a dense sclerotic stroma. These tumor cells are CD20-, ER+ and it was confirmed these tumor cells are not lymphoma cells and they are invasive carcinoma of the right breast. Double pathology of DLBCL and invasive carcinoma breast needs special attention for proper management.